Outcome of Therapies in Refractory Convulsive Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Queen Square, London, review the long-term outcome of therapies in refractory convulsive status epilepticus.